LEARNING, PROCESS, PHASE AND GROWTH OF KNOWLEDGE IN ISLAMIC EDUCATIONAL PSYCHOLOGY - Sya'ban, Fadhila Syahri; Winanda, Anggi; Aminullah (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This article aims to integrate the perspectives of Islamic educational psychology and the Qur'an in understanding the learning process and the periodization of human development. In Islamic educational psychology, learning is seen as a process of behavioral change and the acquisition of knowledge, skills, and attitudes, which is based on the theories of tazkiyah, tawhid, tarbiyah, tabi'ah, and fitrah learning. The learning process itself involves pre-learning, learning, and post-learning stages, and goes through the information, transformation, and evaluation phases. Furthermore, this article links the stages of psychological development with the periodization of development in the Qur'an. The Qur'an provides a basic framework for human development from conception to old age, with an emphasis on biological and spiritual aspects. Psychology complements this view by providing details of psychological, cognitive, social, and emotional development at each phase. Islamic education plays an important role in integrating religious values throughout the stages of development, starting from Islamic prenatal care, introduction of basic teachings in childhood, to strengthening understanding and practice of religion in adolescence as preparation for responsible adulthood. This integration provides a holistic understanding of human development that is in line with Islamic values.